Will Schooling Ever Change? School Culture, Distance Learning and the COVID-19 Pandemic - Mikiewicz, Piotr (Routledge Advances in Sociology, 2023)
This book is an insightful meta-narrative about schooling which explores the global natural experiment of the COVID-19 pandemic and its potential impact on school culture. The proposed book discusses how the abrupt and somewhat forced digital transformation of schooling on a global scale (caused by the COVID-19 pandemic) did not change the educational status quo. It states that online teaching and learning failed to transform the role of the key school actors, students and teachers as well as the relationship between them, despite megatrends such as digitalisation, automation and the development of artificial intelligence. This focus text discusses why the global experience of distance education did not translate into a significant qualitative change and provides a theoretical framework which enables the reader to interpret and explain the processes that occurred during distance education, as well as understand why extraordinarily little (if nothing) has changed in school culture. It will appeal to scholars and students from the sociology of education and from education studies, particularly those interested in school culture, innovation in education, online teaching and learning, curriculum studies, and education policy.